Prevalence and Determinants of Vitamin D Deficiency in 9595 Mongolian Schoolchildren: A Cross-Sectional Study - Jorick Bater (MDPI AG, 2021)
Population-based data relating to vitamin D status of children in Northeast Asia are lacking. We conducted a cross-sectional study to determine the prevalence and determinants of vitamin D deficiency in 9595 schoolchildren aged 6–13 years in Ulaanbaatar (UB), the capital city of Mongolia. Risk factors for vitamin D deficiency were collected by questionnaire, and serum 25-hydroxyvitamin D (25[OH]D) concentrations were measured using an enzyme-linked fluorescent assay, standardized and categorized as deficient (25[OH]D <10 ng/mL) or not. Odds ratios for associations between independent variables and risk of vitamin D deficiency were calculated using multivariate analysis with adjustment for potential confounders. The prevalence of vitamins D deficiency was 40.6% (95% CI 39.7% to 41.6%). It was independently associated with female gender (adjusted odds ratio [aOR] for girls vs. boys 1.23, 95% CI 1.11–1.35), month of sampling (aORs for December–February vs. June–November 5.28 [4.53–6.15], March–May vs. June–November 14.85 [12.46–17.74]), lower levels of parental education (P for trend <0.001), lower frequency of egg consumption (P for trend <0.001), active tuberculosis (aOR 1.40 [1.03–1.94]), household smoking (aOR 1.13 [1.02 to1.25]), and shorter time outdoors (P for trend <0.001). We report a very high prevalence of vitamin D deficiency among Mongolian schoolchildren, which requires addressing as a public health priority.